2021
DOI: 10.1101/2021.03.24.436779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translocation of chloroplast NPR1 to the nucleus in retrograde signaling for adaptive response to salt stress in tobacco

Abstract: Chloroplasts play a pivotal role in biotic and abiotic stress responses, accompanying changes in the cell reduction/oxidation (redox) state. Chloroplasts are an endosymbiotic organelle that sends retrograde signals to the nucleus to integrate with environmental changes. This study showed that salt stress causes the rapid accumulation of the nonexpressor of pathogenesis-related genes 1 (NPR1) protein, a redox-sensitive transcription coactivator that elicits many tolerance responses in chloroplasts and the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Apoplastic ROS, such as H 2 O 2 itself as a signaling molecule, instigates a change in gene expression in the nucleus. For instance, the nonexpressor of pathogenesis-related genes 1 (NPR1) protein, a redox-sensitive transcription coactivator, primarily localized in the cytoplasm in both Arabidopsis and tobacco, transported to the nucleus in response to salt stress to function as a coactivator of gene transcription [ 99 , 100 , 101 ]. Recently, it was shown that a nuclear translocation of GmMPK6 from the cell membrane during high salinity treatment in soybean seedlings can be blocked by DPI treatment, suggesting that the nuclear translocation is mediated by Rboh-dependent H 2 O 2 [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoplastic ROS, such as H 2 O 2 itself as a signaling molecule, instigates a change in gene expression in the nucleus. For instance, the nonexpressor of pathogenesis-related genes 1 (NPR1) protein, a redox-sensitive transcription coactivator, primarily localized in the cytoplasm in both Arabidopsis and tobacco, transported to the nucleus in response to salt stress to function as a coactivator of gene transcription [ 99 , 100 , 101 ]. Recently, it was shown that a nuclear translocation of GmMPK6 from the cell membrane during high salinity treatment in soybean seedlings can be blocked by DPI treatment, suggesting that the nuclear translocation is mediated by Rboh-dependent H 2 O 2 [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear how theanine induced the expression of these genes. Recently, the retrograde signaling from chloroplast to nucleus was reported to be critical for salt stress tolerance in plants (Park and Seo, 2021;Zhuang et al, 2021). This retrograde signaling is required for the induction of ROS scavenging pathway genes such as CSD2 (Zhuang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Then, that H 2 O 2 is converted into H 2 O and oxygen by ascorbate peroxidases (APXs), catalases (CATs), as well as other free radical scavengers (Bose et al, 2013). ROS imbalance is harmful to plants; however, H 2 O 2 is also involved in the chloroplast-to-nucleus retrograde signaling which is critical for salt stress response in plants (Park and Seo, 2021;Zhuang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…NPR1, the primary SA receptor protein, is important for many physiological processes as well as different types of plant disease resistance. It is interesting to note that saline stress causes rapid accumulation of the NPR1 protein in the chloroplast stroma, which prevents stress from causing a reduction in the photosynthetic capacity in a redox-dependent manner [ 125 , 126 ]. This suggests that the NPR1 protein performs an unidentified function in the response to saline stress.…”
Section: Mechanism Comparison Of Sa In Saline and Biotic Stressmentioning
confidence: 99%